The Effectiveness of 3d Hologram Media on Elementary School Students' Learning Outcomes in Natural and Social Sciences (IPAS) Subjects - Ade Vidianti; Johan Eka Wijaya DN; Anita Adesti; Yelmi Yunarti; Aprilia Yustika Dewi; Ade Dwi Jayanti (CV. Edujavare Publishing, 2026)
The rapid development and advancement of educational science in the modern era have significantly influenced the growth of the educational sector worldwide. This study aims to determine the effectiveness of 3D Hologram Media on Elementary School Students' Learning Outcomes in Natural and Social Sciences (IPAS) subjects. This type of research is quantitative with an experimental method. The form of the experimental approach with a research design is One-Group Pretest-Posttest. The research sample is 14 people. Data collection techniques and tools use multiple-choice tests, analysis techniques using the